Emerging pathology: pulmonary disease caused by Mycobacterium xenopi – a challenge in clinical practice - Pešut, Dragica P.; Stević, Ruža S.; Marić-Živković, Jasmina Dj; Savić, Biljana Dj; Nagorni-Obradović, Ljudmila M. (Vojnosanitetski pregled, 2020)
Abstract Introduction. Human nontuberculous mycobacteria (NTM) or environmental mycobacteria related disease is on increase. Risk factors are unclear and associations are observed in relation to climate differences, population density, or host susceptibility. With availability of molecular techniques for NTM identification, we faced emergence of NTM pulmonary cases. The work is an invitation more to colleagues to enroll the rare NTM cases into large study group. Case report. During an episode of productive cough and fever in a 73-year-old HIV-negative man smoker with minimal sequellae of pulmonary tuberculosis, sputum smears were acid fast bacilli positive on direct microscopy. The Löwenstein-Jensen culture results were positive with 20, 30 and 50 colonies, and molecular identification confirmed Mycobacterium xenopi (M. xenopi). Standard chest radiography showed no signs of active lesions. Examination was completed with bronchoscopy and thorax multi-slice computed tomography (MSCT). Cavitary lesions in the apico-posterior part of the left upper lobe (LUL) were detected. Under treatment (rifampicin, ethambutol, clarithromycin) sputum conversion was achieved, but irregular cavitation in the LUL remained at MSCT after 6 and after 12 months with signs of minimal regression. Patient’s general condition only mildly improved and asthenia remained. Observed risk factors were previous pulmonary disease, tobacco smoking, malnutrition and prolonged emotional stress. Conclusion. M. xenopi related pulmonary disease, difficult to cure and with uncertain prognosis, is a challenge in clinical practice. Since treatment is still controversial, more randomized clinical trials are needed. Current international multicentre approach might be a good option for a larger sample size and development of new guide.